2008
DOI: 10.1677/joe-08-0070
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in vascular function: implication of endothelium-derived hyperpolarizing factor

Abstract: The vascular endothelium plays a crucial role in the regulation of vascular homeostasis by controlling vascular tone, coagulation, and inflammatory responses. These actions are exerted by endothelial factors including nitric oxide, prostacyclin, and endothelium-derived hyperpolarizing factor (EDHF). The greater incidence of cardiovascular disease (CVD) in men and postmenopausal women compared with premenopausal women implies a vasoprotective phenotype of females, which may be influenced by sex hormones. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 238 publications
3
40
0
Order By: Relevance
“…This is a plausible association that plays a crucial role in vascular homeostasis, which may be regulated by sex hormones, especially estrogen 26. Estrogen contributes to regulation of vascular tone, modulates recruitment of circulating cells, effects platelet function, and plays a role in processes responsible for vascular repair 26. Gene variants in women modulate the function of estrogen, its receptors, and are implicated in aspects of cardiovascular inflammation, platelet function, and vascular repair 26, 27…”
Section: Discussionmentioning
confidence: 99%
“…This is a plausible association that plays a crucial role in vascular homeostasis, which may be regulated by sex hormones, especially estrogen 26. Estrogen contributes to regulation of vascular tone, modulates recruitment of circulating cells, effects platelet function, and plays a role in processes responsible for vascular repair 26. Gene variants in women modulate the function of estrogen, its receptors, and are implicated in aspects of cardiovascular inflammation, platelet function, and vascular repair 26, 27…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, speculative and requires further investigation. Estrogen improves vascular tone by decreasing myointimal smooth muscle cell proliferation (40), inhibiting tumor necrosis factor-␣-induced apoptosis in endothelial cells, (32), and inducing NOS3 in different tissues (45,50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have described the inhibition of iNOS by HP (Tedeschi et al, 2003;Saad et al, 2008;Kraus et al, 2010). Endothelial cell xantine oxidase forms ROS (Villar et al, 2008). A set of experiments has been done on xantine oxidase system of vascular tissue by using commercially available form of HP and this study has shown a dose-dependant ROS suppression (Hunt et al, 2001).…”
Section: Discussionmentioning
confidence: 74%
“…The vascular endothelium has a crucial role in the modulation of the vascular functions such as contraction and relaxation of the vascular smooth muscle (Demirci et al, 2005;Moncada and Higgs, 2006;Demirci et al, 2008;Villar et al, 2008). This delicate balance is achieved by synthesizing and secreting vasoactive agents, mainly nitric oxide (NO), prostaglandins, endothelium-derived hyperpolarizing factor (EDHF) (Moncada & Higgs, 2006;Villar et al, 2008) and endothelins (Whittle & Moncada, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation